Pediatric Trauma Arrival Times and the Swing Shift. Issue 1 (January 2022) - Berg, Patrick; Chestovich, Paul J.; Jones, Stephanie; Allenback, Gayle; McNickle, Allison G.; Saquib, Syed F.; Fraser, Douglas R.; Kuhls, Deborah A.
Abstract : Background: Trauma center staff and trainees are often assigned to a day and night shift. However, for adult trauma, the swing shift has been found to offer superior clinical exposure compared with a standard day or night shift for trainees. We characterized patterns in pediatric trauma arrival times based on the hour, weekday, and month and studied whether or not the swing shift also maximizes exposure to hands-on experiences in managing pediatric trauma. Methods: We performed a retrospective review of the trauma database at our urban, level 2 pediatric trauma center. We identified all the pediatric trauma activations in the last 13 years (2006–2018). A retrospective shift log was created, which included day (7:00 AM to 7:00 PM), night (7:00 PM to 7:00 AM), and swing (noon to midnight) shifts. The shifts were compared using the Wilcoxon match-pairs signed rank test. Weekends data were also compared with weekdays, and comparisons were also made for pediatric patients with Injury Severity Scores (ISS) >15. Results: There were 3532 pediatric patients identified for our study. The swing shift had 1.98 times more activations than the night shift, and 1.33 more than the day shift ( P < 0.001). The swing shift was also superior to both the day and night shifts for exposure to patients with Injury Severity Score greater than 15 ( P < 0.001). Weekend days had 1.28 times more trauma than the weekdays ( P < 0.001). Peak arrival time was between the hours of 3:00 PM and 9:00 PM, and patient age did not have an effect on this trend. Conclusions: Experience in managing pediatric trauma patients will improve for trainees who utilize the swing shift. In addition, the hours between 3:00 PM and 9:00 PM on weekends may represent a time of particularly high likelihood of pediatric trauma arrivals, which may require extra staff and hospital resources. Level of Evidence: Therapeutic Study, Level IV